ANALISIS ARAH DAN PERLAKUAN SERAT TAPIS SERTA RASIO EPOXY HARDENER TERHADAP SIFAT FISIS DAN MEKANIS KOMPOSIT TAPIS/EPOXY - Lokantara, Putu; Suardana, Ngakan Putu Gede (Jurnal Energi Dan Manufaktur, 2012)
Tapis kelapa (Coconut filter) as natural fiber, in this time its resources very copius but no longer be exploited and thrown off hand as waste though in fact its used for other material dissimilar inovatif and high economic valuable that is as one of natural fiber alternative to be composite. The objective of this research is to investigate the behavior changing of physical and mechanical properties of composite tapis kelapa as reinforcement and epoxy 7120 with hardener Versamid 140 as matrix. The fiber is treated with the chemical NaOH and KMnO4 with percentage 0.5%, 1%, and 2% in weight, respectively. The ratio of epoxy and hardener is 7:3 and 6:4, and fiber orientation 0o, 45o, dan 90o. For testing of the speciment in tensile test with ASTM standard D3039 and three point bending test with ASTM standard D790. The result of this research obtained that fiber treatment with KMnO4 give the better effect to machine properties compared to NaOH. Variation of percentage 0.5%, 1%, and 2% NaOH and KMnO4 give the effect in fiber surface which higher percentage make the cleaner of surface, decrease of wax contain, and roughness of fiber surface so that stronger of linkage of fiber and matrix and increase of tensile strength, bending strength, and bending modulus of the composite. The highest tensile strength, modulus of elasticity and bending strength are 70.23 MPa, 446.24 GPa and 97.81 MPa respectively reached at composite with ratio epoxy/hardener 7:3; by 2% KMnO4 and fiber orientation 45o. While the highest modulus of elasticity is 385.48 GPa reached at composite with the ratio epoxy/hardener 6:4; 2% KMnO4 and fiber orientation 90o. Keywords: Tensile Strength, bending strength, ratio of epoxy/hardener, NaOH, KMnO4
Keywords: Kekuatan tarik, kekuatan bending, ratio epoxy/hardener, NaOH, KmnO4